3-Aryl-2-(thiazol-2-yl)acrylonitriles assembled with aryl/hetaryl rings: Design of the optical properties and application prospects. (January 2021) - Eltyshev, Alexander K.; Dzhumaniyazov, Timur H.; Suntsova, Polina O.; Minin, Artem S.; Pozdina, Varvara A.; Dehaen, Wim; Benassi, Enrico; Belskaya, Nataliya P.
Abstract: New fluorescent thiazoles were designed and synthesized based on a 3-aryl-2-(thiazol-2-yl)acrylonitrile core. Three synthetic approaches were developed to introduce specific combinations of substituents at the 2-, 4- and 5-thiazole positions. The obtained thiazolyl-2-acrylonitriles exhibited a wide range of fluorescent colours (from green to red), long wavelength maxima and intensity depending on the combination of the substituents located at rings A, B and C. The expanded photophysical investigation established the best substituent combinations to increase their emission. Absorption and emission were studied in solvents with different polarities, as well as in DMSO-water and dioxane-water mixtures. The thiazoles showed multifunctional properties and exhibited good emission in the solid phase and in suspension (aggregation induced enhancement emission/AIEE effect). Photophysical investigations revealed a large Stokes shift, significant positive solvatochromism, and the tunability of the colour and intensity. Sharp strengthening of the emission intensity of the thiazoles was observed upon stimulation with some acid (H2 SO4 and BF3 ·OEt2 ) in solvents and in the solid phase (HCl). State-of-the-art quantum mechanical calculations were performed to interpret the experimental findings. Biological experiments revealed the good penetration of the thiazoles into living cells and the accumulation both in lysosomes and, to a lesser extent, near membranes. Graphical abstract: Image 1 Highlights: A series of new varicolored fluorophores was obtained. The expanded spectral investigation and quantum mechanical calculations were performed. Relationships between structure – fluorescence maxima and intensity were established. ICT, solvatochromism, acidochromism in solution and in solid were investigated. Penetration into the living cells open application for bioimaging or theranostics.